2005
DOI: 10.1258/095646205774763135
|View full text |Cite
|
Sign up to set email alerts
|

Reported condom use and condom use difficulties in street outreach samples of men of four racial and ethnic backgrounds

Abstract: The epidemiology of the HIV/AIDS epidemic in the United States has focused research attention on lesbian, gay, bisexual and transgendered communities as well as on racial and ethnic minorities. Much of that attention has, however, been focused on specific racial and ethnic groups and specific sexual minorities. We report on the results of a study that examined the association between condom use and partnership types among men from four major racial/ethnic groups.Self-reported data on sexual identity (homosexua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 4 publications
2
20
0
Order By: Relevance
“…The finding suggests that Bahamian men with high levels of masculine ideology endorsement were less likely to practice safer sex behaviors than men with lower levels of masculine ideology endorsement, consistent with the research hypothesis. The results of this study implied negative attitudes towards safer sex behaviors and support those of other studies in the literature that directly linked masculine ideology to safer sex behaviors (Essien et al, 2005;Figueroa et al, 2005;Kennedy & Roberts 2009). In a study with 101 men and 199 women ages 18-24 in northern KwaZulu/Natal province, Harrison and colleagues (2006) found that the men in the study with less masculine norms were more likely to engage in consistent condom use than men with more masculine norms.…”
Section: Masculine Ideology and Safer Sex Behaviorssupporting
confidence: 82%
See 1 more Smart Citation
“…The finding suggests that Bahamian men with high levels of masculine ideology endorsement were less likely to practice safer sex behaviors than men with lower levels of masculine ideology endorsement, consistent with the research hypothesis. The results of this study implied negative attitudes towards safer sex behaviors and support those of other studies in the literature that directly linked masculine ideology to safer sex behaviors (Essien et al, 2005;Figueroa et al, 2005;Kennedy & Roberts 2009). In a study with 101 men and 199 women ages 18-24 in northern KwaZulu/Natal province, Harrison and colleagues (2006) found that the men in the study with less masculine norms were more likely to engage in consistent condom use than men with more masculine norms.…”
Section: Masculine Ideology and Safer Sex Behaviorssupporting
confidence: 82%
“…Other studies have suggested that the primary reasons for failure to use condoms ranges from embarrassment at purchase (Bell, 2009;Higuchi & Nakamura, 2010;Moore et al, 2008); a belief that condoms reduce sensitivity and pleasure (Carballo-Diéguez et al, 2011;Crosby, 2005;Randolph, Pinkerton, Bogart, Cecil, & Abramson, 2007); gender and ethnicity (Essien, Ross, Fernandez-Esquer, & Williams, 2005;Figueroa et al, 2005;Kennedy & Roberts, 2009;Lewis, Melton, Succop, & Rosenthal, 2000); lack of condom self-efficacy (Brodbeck, Vilén, Bachmann, Znoj, & Alsaker, 2010;Gillespie-Johnson, 2008;Hoffman et al, 2008 ); and age (Davis, Duncan, Turner, & Young, 2001;Dehne & Riedner, 2005;Flood, 2003;Hulton, Cullen, & Khalokho, 2000;.…”
Section: Condom Use and Other Influences On Safer Sex Behaviormentioning
confidence: 99%
“…Fourteen studies examined rates of UAI, and all found that API MSM engaged in similar rates of UAI compared to White MSM or race/ethnicity was not associated with UAI [7,10,13,[15][16][17][18][19][20][21][22][23][24][25]. The San Francisco/Berkeley Young Men's Study found that 27% of API young men who have sex with men (YMSM) reported UAI in the past 6 months compared to 28% of White YMSM [10].…”
Section: Resultsmentioning
confidence: 99%
“…Much can be learned from condom users, and yet, well into the HIV epidemic's third decade, a gap continues to exist in the literature to explain condom use. 6,7,10,11,14,45 Exploring some of the practical aspects of condom use, such as acquisition, preferences, and other considerations that we were unable to examine (e.g., slippage, breakage, and the use of lubricants), among gay and bisexual men and other populations at increased sexual risk and for whom condom use is recommended may prove beneficial. We did not measure use of the female condom which has been suggested as a barrier method for anal sex among MSM; although rates have been reported to be low, 46 further exploration of the experiences of using a female condom may provide important insights.…”
Section: Rhodes Et Al 866mentioning
confidence: 99%
“…[1][2][3][4] Factors that affect a gay or bisexual man's decision to use a condom include: knowledge about HIV and STD transmission and prevention, intention to use a condom, condom availability and convenience, ability to ask a partner to use a condom, concurrent substance use, perceptions about spontaneity and sexual sensation and other psychosocial considerations and cultural norms and expectations, and perceived peer attitudes towards condom use. [5][6][7][8][9][10][11][12][13][14] However, before a condom can be used, a condom must be available.…”
Section: Introductionmentioning
confidence: 99%